English usage for clarity - Shinghal, Rajjan (Gurgaon Zorba Books, 2024)
English Usage for Clarity(3y (Bby Rajjan Shinghal offers a guide to English writing focused on clarity and simplicity. Using humorous quotations, Shinghal highlights the differences in styles in American, British, and Indian English. Shinghal encourages authors to adopt a style that feels natural to them, so their writing remains clear and simple. The book explains the meanings and contexts of the Latin terms used commonly in English.s